Poly(lactic-co-glycolic Acid) Nanoparticle Encapsulated 17β-Estradiol Improves Spatial Memory and Increases Uterine Stimulation in Middle-Aged Ovariectomized Rats - Prakapenka, Alesia V.; Quihuis, Alicia M.; Carson, Catherine G.; Patel, Shruti; Bimonte-Nelson, Heather A.; Sirianni, Rachael W. (Frontiers in Behavioral Neuroscience, 2020)
Hormone therapy that contains 17β-estradiol (E2) is used commonly for treatment of symptoms associated with menopause. E2 treatment has been shown to improve cognitive function following the decrease in ovarian hormones that is characteristic of menopause. However, once in circulation, the majority of E2 is bound to serum hormone binding globulin or albumin, becoming biologically inactive. Thus, therapeutic efficacy of E2 stands to benefit from increased bioavailability via sustained release of the hormone. Here, we focus on the encapsulation of E2 within polymeric nanoparticles composed of poly(lactic-co-glycolic) acid (PLGA). PLGA agent encapsulation offers several delivery advantages, including improved bioavailability and sustained biological activity of encapsulated agents. We hypothesized that delivery of E2 from PLGA nanoparticles would enhance the beneficial cognitive effects of E2 relative to free E2 or non-hormone loaded nanoparticle controls in a rat model of menopause. To test this hypothesis, spatial learning and memory were assessed in middle-aged ovariectomized rats receiving weekly subcutaneous treatment of either oil-control, free (oil-solubilized) E2, blank (non-hormone loaded) PLGA, or E2-loaded PLGA. Unexpectedly, learning and memory differed significantly between the two vehicle control groups. E2-loaded PLGA nanoparticles improved learning and memory relative to vehicle control, while learning and memory were not different between free E2 and its vehicle control. These results suggest that delivery of E2 from PLGA nanoparticles offered cognitive benefit. However, when evaluating peripheral burden, E2-loaded PLGA was found to increase uterine stimulation compared to free E2, which is an undesired outcome, as estrogen exposure increases uterine cancer risk. In sum, a weekly E2 treatment regimen of E2 from PLGA nanoparticles increased cognitive efficacy and was accompanied with an adverse impact on the periphery, effects that may be due to the improved agent bioavailability and sustained biological activity offered by PLGA nanoparticle encapsulation. These findings underscore the risk of non-specific enhancement of E2 delivery and provide a basic framework for the study and development of E2’s efficacy as a cognitive therapeutic with the aid of customizable polymeric nano-carriers.